Реалізація елементів інтегрованого навчання у процесі вивчення польської мови (історичний, географічний, соціальний контексти) - (:unkn) unknown (ХНПУ імені Г. С. Сковороди, 2023)
The article analyses textbooks (by Ukrainian and Polish authors) for learning Polish language. A competent approach to the study of foreign languages in secondary education, higher education and for self-education is taken into account. The authors pay special attention to communicative competences of a wide range, materials of a historical nature. The article draws cross-cultural parallels as well as analyses information on geography and social life. The authors draw attention to the aesthetic design of the books, the relevance of certain topics, their temporal prolongation during the study of Polish as a foreign language at the secondary and higher educational levels, as well as for self-education.
Keywords: Polish as a foreign language, integrated education, adult education, children and youth education, historical context in learning the Polish language